2014
DOI: 10.3892/ol.2014.2614
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma upregulated protein expression is involved in the pathogenesis of human breast carcinogenesis

Abstract: In the last decade, the overexpression of hepatoma upregulated protein (HURP) has been reported in hepatocellular carcinoma, adrenocortical tumors and urogenital carcinoma. However, the role of HURP in breast cancer remains unknown. In the present study, a comprehensive analysis was performed to examine the HURP expression level in 43 breast cancer tumor samples and paired adjacent normal tissues. The correlation between the HURP expression level and the clinicopathological characteristics was evaluated. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This is further supported by the observation that knockdown of HURP leads to inhibition of proliferation of human pharyngeal squamous carcinoma cells (37). The tumorigenic activity of HURP has also been reported in breast cancer (24), hepatocellular carcinoma (HCC) (25) and ATC (30,38) indicating its important role in human cancer development.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This is further supported by the observation that knockdown of HURP leads to inhibition of proliferation of human pharyngeal squamous carcinoma cells (37). The tumorigenic activity of HURP has also been reported in breast cancer (24), hepatocellular carcinoma (HCC) (25) and ATC (30,38) indicating its important role in human cancer development.…”
Section: Discussionmentioning
confidence: 58%
“…HURP protein is encoded by HURP or DLGAP5 (Disks large-associated protein 5) gene, located on chromosome 14q22.3. HURP is a MAP protein associated with kinetochore MTs, that plays a critical role in spindle assembly, chromosome congression, alignment and segregation (20)(21)(22)(23) and has a previously reported to be involved in tumorigenesis (24,25). Hence, it can be hypothesised that HURP expression may predict response to vinorelbine in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…HURP (Hepatoma Upregulated Protein) was identified as a protein overexpressed in hepatocellular carcinoma, representing a potential oncogene (Tsou et al, 2003). HURP is overexpressed in many other cancer types such as bladder, breast, glioblastoma, prostate and non-small cell lung cancer and has been proposed as a new cancer biomarker (Chen et al, 2014;Eissa et al, 2014;Stangeland et al, 2015;Espinoza et al, 2016;Tagal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we hypothesized that the hepatoma upregulated protein (HURP) plays a role in branching MT nucleation. HURP is another SAF 17,18 , first identified in human hepatocellular carcinoma, and has been implicated in a variety of cancers as a putative oncogene [19][20][21][22][23] . Studies in human cells have demonstrated that HURP is a MT-bundling protein that localizes predominantly to kinetochore fibers (k-fibers) and is important in k-fiber stability and chromosome congression 18,24,25 .…”
Section: Introductionmentioning
confidence: 99%